Composition effects of the German Federal Government on the average top income tax burden - Katrin Scharfenkamp (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2013)
This paper investigates whether the setting of the German top income tax burden is affected by the composition of the Federal Government in terms of connectedness with the national (academic) elite and company network from 1958 to 2011. The results reveal that the percentages of university graduates, former executive board members, as well as the government's average age at the time of decision are related to a lower average top income tax burden. Conversely and surprisingly, an increasing percentage of former members of a supervisory board is associated with a higher average top income tax burden. Interestingly, varying percentages of governmental members with an elitist social background are not aligned with the tax setting. Finally, the higher the difference of mandates between CDU & CSU and those of the SPD in the German Parliament, the lower is the average top income tax burden. – – Dieses Papier untersucht, ob die Festlegung der durchschnittlichen Steuerbelastung deutscher Spitzenverdiener zwischen 1958 und 2011 von der Zusammensetzung der Bundesregierung in Form von Verbindungen zur nationalen (akademischen) Elite und dem Unternehmensnetzwerk beeinflusst wird. Die Ergebnisse zeigen, dass der Anteil an Universitätsabsolventen, früheren Vorstandsmitgliedern und das durchschnittliche Alter der Regierung zum Zeitpunkt der Entscheidung mit einer durchschnittlich niedrigeren Steuerbelastung deutscher Spitzenverdiener verbunden sind. Im Gegensatz hierzu und überraschenderweise ist ein steigender Anteil früherer Aufsichtsratsmitglieder mit einer durchschnittlich höheren Steuerbelastung deutscher Spitzenverdiener verknüpft. Interessanterweise findet sich keine Verbindung eines variierenden Anteils von Regierungsmitgliedern mit elitärem Hintergrund auf Spitzensteuerlast. Schließlich ist die durchschnittliche Steuerbelastung deutscher Spitzenverdiener umso geringer, je höher die Differenz an Bundestagsmandaten zwischen CDU/CSU und SPD ist.
Keywords: D83; D85; H24; P16; 650